An Analysis Figurative Language in Bruno Mars Selected Song Lyric: “It Will Rain” - Patrisia Adma Renda; Desak Putu Eka Pratiwi (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
Language is an important role in human life. Humans need language in order to communicate with other people, interact and also to get information. With the existence of language, every human being can express an idea or ideas, imagination and desires the others. Language serves to unite the relationship between human beings. Language can also be called art because with language, we can express ideas or ideas with literal works commonly used in language arts or commonly called figurative language. Figurative language is a form of parable or not the actual meaning used to write or convey things related to everyday life. This study was conducted to analyze the types of figurative language in Bruno Mars' selected song lyric: